Understanding the Seasonality of Campylobacter Infection among Commercial Broiler Chickens in the United Kingdom - DANIEL PHILLIPS (2024)
Campylobacter spp. are responsible for more cases of gastroenteritis than any other bacteria in humans. Up to 80% of cases originate from poultry. Infections in both chickens and humans follow a seasonal pattern, with an increase in incidence during warmer months. This study aims to determine which causal factors are associated with the seasonal onset of Campylobacter infection in housed chickens. Eleven farms around Herefordshire, UK, were assessed daily for Campylobacter spp. presence by quantitative PCR on swabs taken inside one chicken house per farm. Weather, farm performance indicators and background information about each farm were recorded and used in statistical models to determine the strength of association between parameters and Campylobacter presence. Increased detections of Campylobacter were associated with wooden house construction, and how well temperature and humidity were managed within the house. A subset of four farms was observed for a further seven production cycles, with the same sampling regime as before, along with paired daily swabs of the external farm environment. At slaughter, sections of ilea were collected, tested for Campylobacter presence by PCR and for gut damage using histopathology, and caecal contents were collected for community 16S rRNA gene analysis. Damage to ileal villi was observed primarily in summer months. The diversity of caecal bacteria increased with Campylobacter infection and during summer months. Campylobacter infection of chickens was found to be unlikely to originate from the farmyard environment. Changes to the chicken gut were identified as varying with season, in similar patterns as observed under Campylobacter infection. This study identifies risk factors associated with Campylobacter infection that will guide how future chicken farms may be constructed to improve control of Campylobacter contamination risk factors, and proposes interaction between chicken gut microbiota and the environment inside the chicken house as being a potential explanation of Campylobacter seasonality.